Ab initio nonadiabatic molecular dynamics investigations on the excited carriers in condensed matter systems. (14th March 2019) - Zheng, Qijing; Chu, Weibin; Zhao, Chuanyu; Zhang, Lili; Guo, Hongli; Wang, Yanan; Jiang, Xiang; Zhao, Jin
Abstract : The ultrafast dynamics of photoexcited charge carriers in condensed matter systems play an important role in optoelectronics and solar energy conversion. Yet it is challenging to understand such multidimensional dynamics at the atomic scale. Combining the real‐time time‐dependent density functional theory with fewest‐switches surface hopping scheme, we develop time‐dependent ab initio nonadiabatic molecular dynamics (NAMD) code Hefei‐NAMD to simulate the excited carrier dynamics in condensed matter systems. Using this method, we have investigated the interfacial charge transfer dynamics, the electron–hole recombination dynamics, and the excited spin‐polarized hole dynamics in different condensed matter systems. The time‐dependent dynamics of excited carriers are studied in energy, real and momentum spaces. In addition, the coupling of the excited carriers with phonons, defects and molecular adsorptions are investigated. The state‐of‐art NAMD studies provide unique insights to understand the ultrafast dynamics of the excited carriers in different condensed matter systems at the atomic scale. This article is categorized under: Structure and Mechanism > Computational Materials Science Molecular and Statistical Mechanics > Molecular Dynamics and Monte‐Carlo Methods Electronic Structure Theory > Ab Initio Electronic Structure Methods Software > Simulation Methods Abstract : The non adiabatic molecular dynamics have been used to investigate the excited carrier dynamics and their couplings with complex environment in condensed matter systems.